Conditional relative survival in Waldenström's macroglobulinaemia: a population‐based study in The Netherlands. (4th November 2021) - Amaador, Karima; Kersten, Marie José; Visser, Otto; Posthuma, Eduardus F. M.; Minnema, Monique C.; Vos, Josephine M. I.; Dinmohamed, Avinash G.
Summary: Contemporary diagnosed WM patients, compared to the general population, continue to experience excess mortality regardless of having survived up to 15 years post‐diagnosis. This gradual increase in excess mortality might result from the incurable nature of this disease characterized by multiple relapses throughout the disease course with limited efficacious treatment options in the released/refractory setting.